Advanced control of series voltage compensation to enhance wind turbine ride through - Zhang, S.; Tseng, K.; Choi, San Shing; Nguyen, T.; Yao, D. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
Due to increasing wind power penetration into utility grids, system operators have instituted stringent standards for ride-through compliance of grid-connected wind turbines. Series voltage compensation can be an effective solution to meet the new standards, especially if a low-cost system can be developed. This paper first presents the characteristics of ride-through behavior of doubly fed induction generator (DFIG) using phasor analysis. The analysis is extended to include the effects of generic series voltage compensation. A new control scheme is then described and analyzed, which allows relatively low-energy ratings in the series compensator, thereby significantly lowering the overall system cost. The new controller enables the DFIG with the compensator to provide the reactive power required for system voltage recovery during grid fault, in compliance with the new grid codes. Simulation and experimental results have demonstrated the enhanced performances resulting from the application of the control scheme. © 2011 IEEE.